Attitudes, knowledge, and interest: preparing university students to work in an aging world - Gonçalves, Daniela C. (2013)
Background: The underlying goals of the present study were (i) to assess knowledge of and attitudes towards aging in a sample of Portuguese undergraduate students undertaking various degrees in health and welfare subjects, and (ii) to analyze the extent to which knowledge, attitudes and other factors were associated with interest in working with older adults. Methods: The study was cross-sectional in design. The sample comprised 460 Portuguese undergraduate students enrolled in degrees in nursing, social work, and psychology. They were asked to complete questionnaires and quizzes, which were analyzed using contingency tables and one way analysis of variance for inter-group comparison, and then subjected to multivariate logistic regression analysis. Results: Significant differences emerged between groups on knowledge, attitudes towards aging and interest in working with older adults, with both nursing and social work students displaying more positive attitudes, knowledge, and interest in working with older adults, when compared with psychology students. A regression analysis indicated that attitudes, knowledge, and previous formal contact were significant predictors of interest. Conclusion: Interest in working with older adults was significantly related to positive attitudes, more knowledge and formal previous contact. Positive attitudes towards older adults can be promoted through interaction with faculty members and experts, knowledge acquisition about normative changes with age, and contact with healthy and impaired older adults.